Halogen-Atom Transfer for Visible-Light-Driven Bond Formation: Recent Trends, Challenges, and Opportunities - Cui, Jing; Liu, Weiyi; Niu, Kaikai; Xing, Lingbao (Current Organic Chemistry, 2025)
Halogen-atom transfer (XAT) has emerged as a powerful and versatile radical-based strategy for both the activation of carbon-halogen bonds and the construction of new bonds under mild, catalyst-controlled conditions. Recent breakthroughs in photocatalysis have reinvigorated interest in this classical radical process by enabling efficient light-induced XAT pathways that circumvent the inherent limitations of traditional single-electron transfer (SET) mechanisms. This review highlights recent advances in XAT-mediated bond formation, with a focus on C-C, C-N, C-O, C-S, C-Cl, C-D, C=C, and C-P bond construction enabled by visible-light photocatalysis. Emphasis is placed on mechanistic innovation-particularly the use of α-aminoalkyl, boryl, aryl and silyl radicals as XAT initiators-and on the strategic merger of photoredox catalysis with transition metal systems. These developments have unlocked previously inaccessible reactivity patterns, including regioselective eliminations of alkenes, radical carbonylation, multicomponent couplings, and tandem cyclizations. The emerging utility of XAT in constructing complex molecules from simple halide precursors underscores its growing impact on modern synthetic design. By dissecting key mechanistic principles and categorizing bond-forming applications, this review provides a forward-looking perspective on the synthetic potential of halogen-atom transfer and its evolving role in sustainable and programmable molecular construction.
Keywords: Halogen atom transfer (XAT)